2015
DOI: 10.1128/mcb.00107-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screens in Saccharomyces cerevisiae Highlight a Role for Cardiolipin in Biogenesis of Mitochondrial Outer Membrane Multispan Proteins

Abstract: A special group of mitochondrial outer membrane (MOM) proteins spans the membrane several times via multiple helical segments. Such multispan proteins are synthesized on cytosolic ribosomes before their targeting to mitochondria and insertion into the MOM. Previous work recognized the import receptor Tom70 and the mitochondrial import (MIM) complex, both residents of the MOM, as required for optimal biogenesis of these proteins. However, their involvement is not sufficient to explain either the entire import p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…In contrast, the non-bilayerforming phospholipids CL and PE are not required for the biogenesis of Tom22 (64,67). Moreover, the SAM-independent insertion of Tom20 occurs independently of CL, PE, and PC (64,67,68). Thus, PC is specifically required for the SAM-dependent protein import pathways.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the non-bilayerforming phospholipids CL and PE are not required for the biogenesis of Tom22 (64,67). Moreover, the SAM-independent insertion of Tom20 occurs independently of CL, PE, and PC (64,67,68). Thus, PC is specifically required for the SAM-dependent protein import pathways.…”
Section: Discussionmentioning
confidence: 97%
“…In mutants defective in CL or PE synthesis, the biogenesis of outer membrane ␤-barrel proteins is affected (49,50). Whereas CL is also required for the import of proteins with multiple ␣-helical membrane spans into the outer membrane, this import pathway remains largely unaffected in PE-deficient mitochondria (50,51). Furthermore, both phospholipids promote protein transport into the inner membrane and matrix (52)(53)(54)(55)(56)(57).…”
mentioning
confidence: 99%
“…The exact role of the mitochondrial import complex and its mode of action is still unknown (23). Moreover, it has recently been shown that a few proteins may be able to insert into the OM independently of protein factors and that at least in one case this is facilitated by specific lipids (24,25).…”
Section: Edited By Thomas Söllnermentioning
confidence: 99%
“…The exact role of the mitochondrial import complex and its mode of action is still unknown (23). Moreover, it has recently been shown that a few proteins may be able to insert into the OM independently of protein factors and that at least in one case this is facilitated by specific lipids (24,25).Mapping the variation of the import systems in different eukaryotes provides insight into the evolution of the mitochondrial protein import systems, which is key to understanding how the endosymbiotic ancestor of mitochondria converted into an organelle (26 -29 …”
mentioning
confidence: 99%